Implementasi Metode GOST(Government Standard) dan LSB-1(Least Significant Bit) Untuk Mengamankan Teks - Diana, Mia (TIN: Terapan Informatika Nusantara, 2020)
Securing text data is one of the activities carried out so that the text of an information is kept confidential so that it cannot be known by others except those who are entitled to it. One technique that can be done to optimize the security of text data is to combine cryptographic techniques with the steganography technique. Cryptographic techniques function to encode text data that is kept secret through the encryption process. While the steganography technique serves to hide (embedding) encrypted text data into a media such as image, video, audio. This study describes the process of combining cryptographic techniques and steganography techniques in securing sent text. Cryptographic techniques are used to encode secret messages based on the GOST (Government Standard) method and the steganography technique is used to hide encrypted text into a digital image based on the LSB-1 (Least significant bit-1) algorithm. In order to make the process easier, a secret text security application was built using Visual Basic 2008 programming language